Factors contributing to frequent police contact among young people: a multivariate analysis including homelessness, community visibility, and drug use in British Columbia, Canada. (4th March 2022) - Greer, Alissa; Selfridge, Marion; Card, Kiffer; Benoit, Cecilia; Jansson, Mikael; Lee, Zina; Macdonald, Scott
Abstract: There is increasing recognition and attention towards the patterns of police encounters with citizens. In this study, we examine the determinants of being stopped and questioned by the police among a heterogenous sample of adolescents and young adults, who were either people who use drugs and a comparison group, in three non-metropolitan areas of British Columbia, Canada. We conducted bivariate and multivariate analyses to identify the unique variation of frequent police encounters based on demographic characteristics and potential confounders. Of 448 young people, 92.0% reported at least one event where police stopped and questioned them in the past five years, and half (49.8%) reported frequent (four or more) police encounters in this time frame. The demographics of race, age, and gender were not significant in the analyses, whereas weekly illicit drug use, homelessness, and high visibility in the community were significantly related to frequent police encounters. Findings suggest that, controlling for demographic variables, young people who have precarious housing, use drugs, and have higher community visibility are at higher risk of police contact. Our findings also show when street involvement and drug use are controlled for, race does not determine police encounters.